Implementation of Compliance Online System towards Good Corporate Governance at PT Kilang Pertamina International Based on Legislation - Luky Tri Sasongko; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2025)
This research examines the principles of digital-based Good Corporate Governance at PT Pertamina International Refinery RU IV Cilacap in accordance with Indonesian legislation. The implementation of Good Corporate Governance is believed to provide the importance of implementing Good Corporate Governance in increasing transparency, accountability, responsibility, independence and fairness in the company’s operations to overcome abuse of authority. This research uses an empirical juridical method with a qualitative approach, utilizing primary data obtained through interviews with resource persons from PT Kilang Pertamina Internasional RU IV Cilacap, as well as secondary data from legal documents and related literature. The results show that the implementation of digital-based Good Corporate Governance, especially through the Compliance Online System (Compols), contributes significantly to operational effectiveness and prevention of abuse of authority at PT Kilang Pertamina Internasional RU IV Cilacap.